A kind of sintered stone alkali activated lightweight high-strength concrete and its preparation and construction method
By using composite alkali of sintered stones and standard sand in sponge urban buildings, lightweight high-strength concrete is stimulated, combined with air-induced water-reducing agent, the problems of low strength and poor uniformity in the existing technology are solved, and high strength and good heat insulation are achieved Its easy construction effect meets the multiple performance needs of sponge cities and improves waste slag utilization.
Patent Information
- Application Number
- CN202310288680.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-03-22
AI Technical Summary
In the application of existing alkali-induced lightweight concrete in sponge cities, there are problems such as low strength, poor uniformity, insufficient engineering targeting and insufficient utilization of waste slag, which is difficult to meet the problems of sponge cities' water seepage, compression resistance, wear resistance, heat insulation and easy maintenance. need.
Using sintered stones and standard sand as coarse and fine aggregates, combined with composite alkali excitation technology and air-induced water reducing agents, lightweight high-strength concrete with high strength and good thermal insulation performance is prepared, and the uniformity of the concrete is ensured through specific construction methods. Be strong and fast.
It has achieved a breakthrough in engineering technology for characteristic concrete in sponge cities, with advantages of local materials, convenient construction, early strength, fast and hardness, uniform quality, and good frost resistance. At the same time, it has improved the utilization rate of solid waste and reduced the engineering cost.
Smart Images

Figure CN116161916B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sponge city building materials, and in particular to a sintered stone alkali-activated lightweight high-strength concrete and a preparation and construction method thereof. Background Art
[0002] Sponge city is an innovative manifestation of promoting green building construction, low-carbon city development, and smart city formation. It is an organic combination of modern green new technologies and social, environmental, and humanistic factors under the background of the new era. Sponge city building materials need to have excellent water seepage, pressure resistance, wear resistance, anti-skid, comfort and easy maintenance, heat insulation, noise absorption, etc., which can effectively reduce the urban heat island effect. It is necessary to consider that the material can have excellent water seepage, pressure resistance, wear resistance, and anti-skid functions, as well as the maintenance, heat insulation, and noise absorption performance of the material, while at the same time being low-cost and easy to promote. At present, there are few research results in this area.
[0003] Patent application CN202210180608.1 discloses a lightweight expanded clay concrete and a preparation method thereof, comprising the following components in parts by weight: 283-508 parts of sand, 189-218 parts of expanded clay, 170-180 parts of water, 48-60 parts of slag powder, 37-49 parts of fly ash, and 7.35-12.27 parts of admixtures. Patent application CN202111459286.6 discloses a ceramsite concrete and a preparation method thereof, comprising components by weight: 300-400 parts of cement, 250-350 parts of modified ceramsite, 10-20 parts of admixture, 800-1000 parts of fine aggregate, 150-250 parts of water, 80-120 parts of sodium bentonite and 80-120 parts of fiber, mixing and stirring in the above proportions to obtain a mixed solution, soaking natural ceramsite loaded with nano magnesium oxide in the mixed solution, and drying to obtain modified ceramsite; Patent application CN201510810774. 5 discloses a modified alkali-activated cementitious material, which comprises, by weight, 100 parts of fly ash and slag, 25-50 parts of alkali activator, 0.5-2 parts of retarder, and 2-15 parts of polymer rubber powder, wherein the solid content of the alkali activator is 30%-40%, and the polymer rubber powder is selected from one or more of butadiene-styrene copolymer rubber powder, styrene-acrylic acid copolymer rubber powder, acrylate copolymer rubber powder, ethylene-vinyl acetate copolymer rubber powder, vinyl acetate-versatate vinyl ester copolymer rubber powder, or vinyl acetate-versatate vinyl ester-acrylate copolymer rubber powder.
[0004] The above-mentioned existing alkali-activated lightweight concrete has the following defects: (1) The lightweight aggregate is mainly ceramsite and glass beads, with a small amount of ordinary slag. However, the strength of ceramsite and glass beads themselves is relatively low, making it difficult to produce high-strength lightweight concrete; (2) When designing the mix ratio of lightweight concrete, the floating problem of lightweight aggregate is not fully considered, resulting in poor concrete uniformity and serious stratification; (3) Most alkali-activated concrete is designed from a materials science perspective and has no engineering specificity, especially there is no alkali-activated concrete suitable for sponge city projects. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a sintered stone alkali-activated lightweight high-strength concrete and a preparation and construction method thereof. Sintered stone and standard sand are used as coarse and fine aggregates, and composite alkali activation technology and durability improvement measures are adopted to prepare lightweight and insulating concrete suitable for sponge cities. This can solve the current engineering and technical problems of characteristic concrete production in sponge cities, and has the advantages of local materials, convenient construction, early strength and fast hardening, easy drainage, uniform quality, and good frost resistance. It also makes full use of the waste residue after coal combustion, improves the utilization rate of solid waste, and reduces the project cost.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A sintered stone alkali-activated lightweight high-strength concrete comprises the following raw material components by weight: 100 parts of slag, 15-20 parts of alkali activator, 30-100 parts of standard sand, 5-8 parts of water reducer, 25-50 parts of water and 100-200 parts of sintered stone.
[0008] The slag is S95 blast furnace slag, including active SiO2, active Al2O3 and CaO in any proportion not less than 15% of the slag mass, and the water content is not higher than 0.1% of the slag mass.
[0009] The alkaline activator is a composite activator, which includes NaOH and Na2SiO3·9H2O, which are stirred evenly in a mass ratio of 1:9-10, and placed in a dark closed box for 3 to 6 hours after being fully dissolved, and transferred to a 60°C-80°C curing box for standby 0.5-1 hour before use.
[0010] The water reducing agent is an air entraining type water reducing agent, with a water reduction rate greater than 28% and an air entraining amount of 3%-5%.
[0011] The temperature of the water is between 60°C and 80°C.
[0012] The sintered stone has irregular shape, particle size 5mm-30mm, and bulk density 800-1200kg / m 3, cylinder pressure strength 20-28MPa, thermal conductivity 0.3-0.7W / (m·k).
[0013] The preparation method of the sintered stone alkali activated lightweight high-strength concrete specifically comprises the following steps:
[0014] (1) A base activator prepared by mixing NaOH and Na2SiO3·9H2O in a mass ratio of 1:9-10 is stirred and mixed thoroughly, and after being fully dissolved, it is placed in a dark closed box for 3 to 6 hours, and transferred to a 60-80°C curing box for standby use 0.5-1 hour before use;
[0015] (2) weighing slag and standard sand according to the proportion of concrete raw material components, mixing and stirring evenly, and then slowly adding the alkali activator solution prepared in step (1);
[0016] (3) stirring the concrete obtained in step (2) at a speed of 100-150 r / min for 3-5 min, and slowly adding a water reducing agent and water during the stirring process;
[0017] (4) After the concrete obtained in step (3) is stirred to form a viscous concrete liquid, sintered stone is slowly added and the mixture is stirred for 5 minutes to obtain the lightweight high-strength concrete.
[0018] The amount of water used in step (3) = the total amount of water used - the water content in the alkaline activator.
[0019] Based on the construction method of the sintered stone alkali-activated lightweight high-strength concrete prepared above, the construction process specifically includes the following steps:
[0020] Step 1: Prepare water, electricity, pipelines and other construction materials, level the ground of the building template, inject running water into the template to clean the inside, and then apply a layer of lubricating oil on the surface of the template;
[0021] Step 2: pour the prepared mixed concrete, the construction is continuous to avoid segregation and leakage, and ensure that the pouring is completed before the initial setting of the concrete;
[0022] Step 3: After the filling is completed, smooth and clean the poured surface and cover it with plastic film for natural curing.
[0023] The beneficial effects of the present invention are:
[0024] (1) Use sintered stone, the ash left after coal combustion, as coarse aggregate, turning waste into treasure. Sintered stone is a porous and glassy substance in the slag after coal combustion. It has an irregular shape and a particle size of 5mm-30mm. The bulk density of sintered stone is 800-1200kg / m 3, which is close to ordinary slag; but the cylinder compressive strength is 20-28MPa, which is nearly 30% higher than that of ordinary slag. The strength of lightweight concrete made from it as coarse aggregate is 15%-30% higher than that of conventional technology; the thermal conductivity is 0.3-0.7W / (m·k), which has good thermal insulation performance.
[0025] (2) Slag is used as the only powder, which has good activation effect when activated by alkali activator. Slag belongs to the Cao-SiO2-Al2O3 system, and its composition is shown in Table 1. Compared with ordinary Portland cement clinker, slag hydrates faster and has lower hydration heat. 2+ The ion content is high and it is easier to hydrate to form CASH gel; the slag is suitable for a variety of activators (such as sodium silicate, sodium carbonate, sodium sulfate, sodium hydroxide); the slag can effectively inhibit the alkali-aggregate reaction of cement concrete, significantly improve the alkali-aggregate reaction resistance of cement concrete, improve the durability of cement concrete, and improve workability; the generation energy consumption is low, it is green and environmentally friendly, and produces a lower amount of CO2; the generated alkali-activated concrete has a faster strength generation and has good frost resistance and corrosion resistance.
[0026] Table 1 Chemical composition of slag
[0027]
[0028] (3) The composite alkali activator of NaOH and Na2SiO3·9H2O has a good intensity activation effect. The structure and composition of CASH, the product of blast furnace slag alkali activation, depend greatly on the properties of the activator. NaOH activation has a higher Ca / Si ratio and a more ordered structure, which helps the glass or crystal in the slag to undergo structural dissociation, promotes the formation of silicon-aluminum tetrahedrons, and then undergoes a series of chemical reactions to hydrate into calcium silicate gel and hydrated calcium aluminate crystals; while Na2SiO3·9H2O provides hydroxide ions and silicon-aluminum tetrahedral ions to react with calcium ions in the slag to form a gel-like substance through condensation.
[0029] (4) Use air-entraining water-reducing agent to increase strength and durability. The water-reducing agent is a high-efficiency air-entraining water-reducing agent that has a dispersing effect on powder particles, can improve its workability, reduce unit water consumption, improve fluidity, and save powder materials. The addition amount is 0.5%-1.5% of the total mass of the cementitious material. While keeping the slump unchanged, the mixing water consumption is reduced by 10%-20%; or while keeping the water-cement ratio unchanged, the fluidity of the concrete is increased by 25%-35%. At the same time, the composite water-reducing agent can introduce a large number of tiny, closed and evenly distributed bubbles during the mixing process to reduce the bleeding and segregation of the mixture, improve workability, and significantly improve the frost resistance and durability of the concrete. The water-reducing agent can make the concrete have high strength and high durability at the same time. After testing, the basic properties are shown in Table 2.
[0030] Table 2 Basic parameters of concrete durability
[0031]
[0032] In summary, the present invention adopts sintered stone with a porous structure and glassy appearance in the slag after coal combustion. The scheme is simple, the cost is low, and the exploitation of natural resources can be reduced; by introducing a water reducer, the viscosity of the concrete is increased, the floating problem of lightweight aggregate is solved, and the uniformity of the concrete is improved; the concrete has the advantages of early forming, fast strength and hardening, stable quality and high durability, and can be used in the construction of thermal insulation and sponge cities. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a curve diagram showing the effect of the sintered stone content on strength and density.
[0034] Figure 2 This is a characteristic diagram comparing common slag and sintered stone, where: Figure 2 (a) Ordinary slag, Figure 2 (b) Sintered stone. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0036] Example 1
[0037] A sintered stone alkali-activated lightweight high-strength concrete, mainly used in thermal insulation and sponge city engineering construction, contains the following raw material components by weight:
[0038] 100 parts of slag, 15 parts of alkali activator, 100 parts of standard sand, 5 parts of water reducer, 28 parts of water, and 100 parts of sintered stone; the slag is S95 blast furnace slag, including 36.1% of active SiO2, 16.3% of active Al2O3 and 35.6% of CaO by mass, and the water content is not higher than 0.1% of the slag by mass; the alkali activator is a composite activator, containing NaOH and Na2SiO3·9H2O uniformly mixed in a mass ratio of 1:9.29; the water reducer is an air-entraining type water-reducing agent with a water reduction rate of 28% and an air entrainment amount of 5%; the water temperature is 60°C.
[0039] A method for preparing sintered stone alkali activated lightweight high-strength concrete comprises the following steps:
[0040] (1) Mix NaOH and Na2SiO3·9H2O in a mass ratio of 1:9.29 and place in a dark closed box for 3 hours after they are fully dissolved. Transfer to a 60°C curing box half an hour before use for later use;
[0041] (2) weighing slag and standard sand according to the proportion of concrete raw material components, mixing and stirring evenly, and then slowly adding the alkali activator solution prepared in step (1);
[0042] (3) stirring the concrete obtained in step (2) at a speed of 120 r / min for 5 min, and slowly adding a water reducing agent and water during the stirring process;
[0043] (4) After the concrete obtained in step (3) is stirred to form a viscous concrete liquid, sintered stone is slowly added and the lightweight concrete is obtained after continuing to stir for 5 minutes.
[0044] The amount of water used in step (3) = the total amount of water used - the water content in the alkaline activator.
[0045] The sintered stone alkali-activated lightweight high-strength concrete material is sealed and stored for future use. The concrete engineering parameters are shown in Table 3.
[0046] A construction method for sintered stone alkali-activated lightweight high-strength concrete comprises the following steps:
[0047] Step 1: Prepare water, electricity, pipelines and other construction materials, level the ground of the building template, inject running water into the template to clean the inside, and then apply a layer of lubricating oil on the surface of the template;
[0048] Step 2: pour the prepared mixed concrete, the construction is continuous to avoid segregation and leakage, and ensure that the pouring is completed before the initial setting of the concrete;
[0049] Step 3: After the filling is completed, smooth and clean the poured surface and cover it with plastic film for natural curing.
[0050] Table 3 Concrete engineering parameters
[0051]
[0052] Example 2
[0053] A sintered stone alkali-activated lightweight high-strength concrete, mainly used in thermal insulation and sponge city engineering construction, contains the following raw material components by weight:
[0054] 100 parts of slag, 18 parts of alkali activator, 90 parts of standard sand, 6 parts of water reducer, 35 parts of water, and 150 parts of sintered stone; the slag is S95 blast furnace slag, including 36.5% of active SiO2, 16.1% of active Al2O3 and 35.4% of CaO by mass, and the water content is 0.09% of the slag by mass; the alkali activator is a composite activator, containing NaOH and Na2SiO3·9H2O uniformly mixed in a mass ratio of 1:9.36; the water reducer is an air-entraining type water-reducing agent with a water reduction rate of 28% and an air entrainment amount of 5%; the water temperature is 70°C.
[0055] A method for preparing sintered stone alkali activated lightweight high-strength concrete comprises the following steps:
[0056] (1) Mix NaOH and Na2SiO3·9H2O in a mass ratio of 1:9.36 and place in a dark closed box for 5 hours after they are fully dissolved. Transfer to a 60°C curing box half an hour before use for later use;
[0057] (2) weighing slag and standard sand according to the proportion of concrete raw material components, mixing and stirring evenly, and then slowly adding the alkali activator solution prepared in step (1);
[0058] (3) The concrete obtained in step (2) was stirred at a speed of 130 r / min for 4 min, and a water reducing agent and water were slowly added during the stirring process;
[0059] (4) After the concrete obtained in step (3) is stirred to form a viscous concrete liquid, sintered stone is slowly added and the lightweight concrete is obtained after continuing to stir for 4 minutes.
[0060] The amount of water used in step (3) = the total amount of water used - the water content in the alkaline activator.
[0061] The sintered stone alkali-activated lightweight high-strength concrete material is sealed and stored for future use. The concrete engineering parameters are shown in Table 4.
[0062] A construction method for sintered stone alkali-activated lightweight high-strength concrete comprises the following steps:
[0063] Step 1: Prepare water, electricity, pipelines and other construction materials, level the ground of the building template, inject running water into the template to clean the inside, and then apply a layer of lubricating oil on the surface of the template;
[0064] Step 2: pour the prepared mixed concrete, the construction is continuous to avoid segregation and leakage, and ensure that the pouring is completed before the initial setting of the concrete;
[0065] Step 3: After the filling is completed, smooth and clean the poured surface and cover it with plastic film for natural curing.
[0066] Table 4 Concrete engineering parameters
[0067]
[0068]
[0069] Example 3
[0070] A sintered stone alkali-activated lightweight high-strength concrete, mainly used in thermal insulation and sponge city engineering construction, contains the following raw material components by weight:
[0071] 100 parts of slag, 18 parts of alkali activator, 80 parts of standard sand, 7 parts of water reducer, 40 parts of water, and 150 parts of sintered stone; the slag is S95 blast furnace slag, including 35.9% of active SiO2, 16.4% of active Al2O3 and 35.7% of CaO by mass, and the water content is 0.08% of the slag by mass; the alkali activator is a composite activator, containing NaOH and Na2SiO3·9H2O uniformly mixed in a mass ratio of 1:9.56; the water reducer is an air-entraining type water-reducing agent with a water reduction rate of 28% and an air entrainment amount of 5%; the water temperature is 75°C.
[0072] A method for preparing sintered stone alkali activated lightweight high-strength concrete comprises the following steps:
[0073] (1) Mix NaOH and Na2SiO3·9H2O in a mass ratio of 1:9.56 and place in a dark closed box for 5 hours after they are fully dissolved. Transfer to a 70°C curing box half an hour before use;
[0074] (2) weighing slag and standard sand according to the proportion of concrete raw material components, mixing and stirring evenly, and then slowly adding the alkali activator solution prepared in step (1);
[0075] (3) stirring the concrete obtained in step (2) at a speed of 120 r / min for 5 min, and slowly adding a water reducing agent and water during the stirring process;
[0076] (4) After the concrete obtained in step (3) is stirred to form a viscous concrete liquid, sintered stone is slowly added and the lightweight concrete is obtained after continuing to stir for 5 minutes.
[0077] The amount of water used in step (3) = the total amount of water used - the water content in the alkaline activator.
[0078] The sintered stone alkali-activated lightweight high-strength concrete material is sealed and stored for future use. The concrete engineering parameters are shown in Table 5.
[0079] A construction method for sintered stone alkali-activated lightweight high-strength concrete comprises the following steps:
[0080] Step 1: Prepare water, electricity, pipelines and other construction materials, level the ground of the building template, inject running water into the template to clean the inside, and then apply a layer of lubricating oil on the surface of the template;
[0081] Step 2: pour the prepared mixed concrete, the construction is continuous to avoid segregation and leakage, and ensure that the pouring is completed before the initial setting of the concrete;
[0082] Step 3: After the filling is completed, smooth and clean the poured surface and cover it with plastic film for natural curing.
[0083] Table 5 Concrete engineering parameters
[0084]
[0085] Example 4
[0086] A sintered stone alkali-activated lightweight high-strength concrete, mainly used in thermal insulation and sponge city engineering construction, contains the following raw material components by weight:
[0087] 100 parts of slag, 20 parts of alkali activator, 100 parts of standard sand, 8 parts of water reducer, 50 parts of water, and 180 parts of sintered stone; the slag is S95 blast furnace slag, including 36.1% of active SiO2, 16.3% of active Al2O3 and 35.6% of CaO by mass, and the water content is 0.1% of the slag by mass; the alkali activator is a composite activator, containing NaOH and Na2SiO3·9H2O uniformly mixed in a mass ratio of 1:10; the water reducer is an air-entraining type water-reducing agent with a water reduction rate of 28% and an air entrainment amount of 5%; the water temperature is 65°C.
[0088] A method for preparing sintered stone alkali activated lightweight high-strength concrete comprises the following steps:
[0089] (1) Mix NaOH and Na2SiO3·9H2O in a mass ratio of 1:10 and place in a dark closed box for 3 hours after they are fully dissolved. Transfer to a 60°C curing box half an hour before use for later use;
[0090] (2) weighing slag and standard sand according to the proportion of concrete raw material components, mixing and stirring evenly, and then slowly adding the alkali activator solution prepared in step (1);
[0091] (3) The concrete obtained in step (2) was stirred at a speed of 150 r / min for 3 min, and a water reducing agent and water were slowly added during the stirring process;
[0092] (4) After the concrete obtained in step (3) is stirred to form a viscous concrete liquid, sintered stone is slowly added and the lightweight concrete is obtained after continuing to stir for 3 minutes.
[0093] The amount of water used in step (3) = the total amount of water used - the water content in the alkaline activator.
[0094] The sintered stone alkali-activated lightweight high-strength concrete material is sealed and stored for future use. The concrete engineering parameters are shown in Table 6.
[0095] A construction method for sintered stone alkali-activated lightweight high-strength concrete comprises the following steps:
[0096] Step 1: Prepare water, electricity, pipelines and other construction materials, level the ground of the building template, inject running water into the template to clean the inside, and then apply a layer of lubricating oil on the surface of the template;
[0097] Step 2: pour the prepared mixed concrete, the construction is continuous to avoid segregation and leakage, and ensure that the pouring is completed before the initial setting of the concrete;
[0098] Step 3: After the filling is completed, smooth and clean the poured surface and cover it with plastic film for natural curing.
[0099] Table 6 Concrete engineering parameters
[0100]
[0101] The above-mentioned specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification, equivalent substitution and improvement of the present invention within the spirit of the present invention and the protection scope of the claims shall be included in the protection scope of the present invention.
Claims
1. A sintered stone alkali-activated lightweight high-strength concrete for sponge city projects, characterized by: The mixing ratio by weight is: 100 parts of slag, 15-20 parts of alkali activator, 30-100 parts of standard sand, 5-8 parts of water reducer, 25-50 parts of water, and 100-200 parts of sintered stone; The slag is S95 blast furnace slag, including active SiO2, active Al2O3 and CaO in any proportion accounting for not less than 15% of the slag mass, and the water content is not higher than 0.1% of the slag mass; The alkaline activator is a composite activator, including NaOH and Na2SiO3·9H2O; The water reducing agent is an air entraining type water reducing agent; The sintered stone is a porous and glassy substance in the slag after coal combustion. The sintered stone has an irregular shape, a particle size of 5mm-30mm, and a bulk density of 800-1200kg / m 3 , cylinder pressure strength 20-28MPa, thermal conductivity 0.3-0.7W / (m·k); The sintered stone alkali-activated lightweight high-strength concrete for sponge city engineering is prepared by the following preparation method: (1) Fully stir and mix the alkaline activator prepared by NaOH and Na2SiO3·9H2O in a mass ratio of 1:9-10, and place in a dark closed box for 3 to 6 hours after being fully dissolved, and transfer to a 60-80°C curing box for standby 0.5-1 hour before use; (2) weighing slag and standard sand according to the raw material proportion of sintered stone alkali-activated lightweight high-strength concrete, mixing and stirring evenly, and then slowly adding the alkali activator solution prepared in step (1); (3) stirring the concrete obtained in step (2) at a speed of 100-150 r / min for 3-5 min, and slowly adding a water reducing agent and water during the stirring process; (4) After the concrete obtained in step (3) is stirred to form a viscous concrete liquid, sintered stone is slowly added, and stirring is continued for 5 minutes to obtain the sintered stone alkali-activated lightweight high-strength concrete for sponge city engineering; The amount of water used in step (3) = the total amount of water used - the water content in the alkaline activator solution.
2. The sintered stone alkali-activated lightweight high-strength concrete for sponge city engineering according to claim 1, characterized in that: The water reduction rate of the air-entraining water-reducing agent is greater than 28%, and the air-entraining amount is 3%-5%.
3. The sintered stone alkali-activated lightweight high-strength concrete for sponge city engineering according to claim 1, characterized in that: The temperature of the water is between 60°C and 80°C.
4. A method for preparing a sintered stone alkali-activated lightweight high-strength concrete for sponge city engineering according to any one of claims 1 to 3, characterized in that: The specific steps include: (1) Fully stir and mix the alkaline activator prepared by NaOH and Na2SiO3·9H2O in a mass ratio of 1:9-10, and place in a dark closed box for 3 to 6 hours after being fully dissolved, and transfer to a 60-80°C curing box for standby 0.5-1 hour before use; (2) weighing slag and standard sand according to the raw material proportion of sintered stone alkali-activated lightweight high-strength concrete, mixing and stirring evenly, and then slowly adding the alkali activator solution prepared in step (1); (3) stirring the concrete obtained in step (2) at a speed of 100-150 r / min for 3-5 min, and slowly adding a water reducing agent and water during the stirring process; (4) After the concrete obtained in step (3) is stirred to form a viscous concrete liquid, sintered stone is slowly added, and stirring is continued for 5 minutes to obtain the sintered stone alkali-activated lightweight high-strength concrete for sponge city engineering; The amount of water used in step (3) = the total amount of water used - the water content in the alkaline activator solution.
5. A construction method for sintered stone alkali-activated lightweight high-strength concrete for sponge city engineering prepared based on claim 3, characterized in that: The construction process specifically includes the following steps: Step 1: Prepare the construction materials for water, electricity and pipelines, level the ground of the building template, inject running water into the template to clean the inside, and then apply a layer of lubricating oil on the surface of the template; Step 2: pour the prepared mixed concrete, the construction is continuous to avoid segregation and leakage, and ensure that the pouring is completed before the initial setting of the concrete; Step 3: After the filling is completed, smooth and clean the poured surface and cover it with plastic film for natural curing.
Citation Information
Patent Citations
Modified alkali-activated cementing material and preparation method thereof
CN105461265A
Ceramsite concrete and preparation method thereof
CN114044693A
Lightweight ceramsite concrete and preparation method thereof
CN114538955A
A Method For Preparing The Fast-Hardening Early-Strength High-Performance All-Solid Waste Concrete
AU2020101143A4
Premixed concrete of using coal gangue slag to replace partial natural sands
CN101885599A
